Odpowiedzi

2010-02-17T16:22:17+01:00
A) 6a-(2a-3b)+(a-6b)= 4a+3b+a-6b = 5a-3b



b) -(2-5x)+(1-4x)-x=-2+5x+1-4x-x=-1



c) (a-b)+(3a+2b)-(4a-3b)=4a+b -4a+3b=4b


d) -(3x-4y)-(2x-3y)+(-y+4x)= -5x+7y-y+4x= 6y -x

e) a-[b-(a-b)-a]=a-[b-a+b-a]= -2b+3a


f) [-(-x)-(x-y)+(y+x)]=x-x+y+y+x=2y+x

1 4 1
2010-02-17T16:26:15+01:00
A) 6a-(2a-3b)+(a-6b)= 6a - 2a + 3b + a - 6b = 5a - 3b
b) -(2-5x)+(1-4x)-x= - 2 + 5x + 1 - 4x - x = - 1
c) (a-b)+(3a+2b)-(4a-3b)= a - b + 3a + 2b - 4a + 3b = 4b
d) -(3x-4y)-(2x-3y)+(-y+4x)= - 3x + 4y - 2x + 3y - y + 4x = - x + 6y
e) a-[b-(a-b)-a]= a - (b - a + b - a - a) = a - b + a - b + a + a = 4a - 2b = 2(2a-b)
f) [-(-x)-(x-y)+(y+x)]= (x - x + y + y + x) = x - x + y + y + x = x + 2y
1 5 1